Media and PR - HO139 - 202101 - Velapatiño Castro, María Ysabel (2021)
It is a Hospitality and Administration program- elective course of a theoretical and practical nature. Nowadays, Media and Public Relations are vital communication tools and strategies, as well as Corporate Image positioning. During the semester, the course will allow you to master processes, tools, applications and functions such as identifying the target audience, as well as the impact and application of communication and mass media tools.